2017
DOI: 10.1016/j.chb.2017.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Why do people buy virtual goods: A meta-analysis

Abstract: During the last decade, virtual goods have become an important target of consumption online (especially in games, virtual worlds and social networking services) amongst physical and digital goods. In this study we investigate the question of why do people purchase virtual goods by conducting a metaanalysis of the existing quantitative body of literature (24 studies) on the topic. The meta-analysis revealed an important aspect of value of virtual goods: contrary to traditional goods, the reasons why people purc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 58 publications
7
113
0
2
Order By: Relevance
“…Use of virtual items linked to player's game accounts as stakes in gambling activities. Hamari and Keronen, 2017;Holden et al, 2016;Lehdonvirta and Castronova, 2014 Esports…”
Section: Point Of Convergence Description Referencesmentioning
confidence: 99%
“…Use of virtual items linked to player's game accounts as stakes in gambling activities. Hamari and Keronen, 2017;Holden et al, 2016;Lehdonvirta and Castronova, 2014 Esports…”
Section: Point Of Convergence Description Referencesmentioning
confidence: 99%
“…Seo [10] found that professional gamers view computer game consumption as neither leisure nor work. Hamari and Keronen [11] used the random effects model to study a platform and found that enjoyment and prolonged use of the platform were more important predictors for purchases in virtual worlds than in games. Castronova et al [12] found that fantasy gamers may well be economically normal.…”
Section: Research Theorymentioning
confidence: 99%
“…Individuals may see virtual consumption equal to real-world consumption activies as virtual consumption reflects some economic aspects of real-world consumption like business activity, consumer activity, currency and economy (Jung and Pawlowski, 2014b). Here the purchase of virtual goods are tightly connected to the platform; the value of virtual goods are equivalent with the environment where they are usable in, so the service design is an important factor for game developers to increase in-game purchases (Hamari and Keronen, 2017). Ho and Wu (2012) found game type itself is a moderating variable that affects intent to purchase virtual goods.…”
Section: Literature Reviewmentioning
confidence: 99%